2022
DOI: 10.3389/fpsyg.2021.746558
|View full text |Cite
|
Sign up to set email alerts
|

Using Data Mining Approach for Student Satisfaction With Teaching Quality in High Vocation Education

Abstract: High vocation education is an important foundation for China to cultivate high teaching quality and technical and skilled talents. In the new era, the acceleration of the development of modern vocational education is put in a more prominent position. It is proposed that we should adhere to moral education, closely combine this with the needs of technological change and industrial upgrading, constantly improve the quality of high vocational education teaching, and cultivate more technical and skilled talents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Schultz's ( 1960 ) innovative research on educational investment and return has gone through two stages. The first stage is related to the growth effect of quality education supported by Solmon ( 1985 ), Doménech-Betoret ( 2018 ), Shu et al ( 2020 ), and Chen et al ( 2022 ). The second stage is linked to the growth effect of the scale of education, which is prioritized (Romer, 1986 ; Lucas, 1988 ; Fassbender and Leyendecker, 2018 ; Navarro-Carrillo et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schultz's ( 1960 ) innovative research on educational investment and return has gone through two stages. The first stage is related to the growth effect of quality education supported by Solmon ( 1985 ), Doménech-Betoret ( 2018 ), Shu et al ( 2020 ), and Chen et al ( 2022 ). The second stage is linked to the growth effect of the scale of education, which is prioritized (Romer, 1986 ; Lucas, 1988 ; Fassbender and Leyendecker, 2018 ; Navarro-Carrillo et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We utilize investigation data from vocation education as an instance to analyze the present state of the teaching quality of the fundamental entrepreneurship curriculum using mining technology analysis tools. The findings of this study may be utilized in high vocation college education for student information, educational approach, student satisfaction with overall education, and educational quality, as well as to improve the teaching quality of entrepreneurial foundation curriculum [22]. The findings connected to educational reform for enhancing graduate employability and human development will benefit vocational colleges, firms, representatives, instructors, and economics and trade graduates based on these findings.…”
Section: Relative Workmentioning
confidence: 76%
“…Kang et al (2016) showed that the overwhelming majority of students believed that the main reason why entrepreneurship education was unsatisfactory was that the shortage of innovative and high-quality teachers affected the quality of entrepreneurship curriculum. Moreover, other research results also showed that students' satisfaction with entrepreneurship education is positively correlated with the satisfaction degree of entrepreneurship course construction to students and society (Li, 2017;Pang et al, 2018;Chen et al, 2021), and with the degree to which entrepreneurship curriculum are combined with professional curriculum (Huang and Du, 2020). While, the importance of agricultural development to developing countries has also led to a growing need for students with entrepreneurial knowledge and skills (Hosseini and Pouratashi, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Our results are consistent with previous studies. Chen et al (2021) proved that teaching methods and teachers' entrepreneurial attitude are the two biggest variables affecting students' satisfaction with entrepreneurial education. Kang et al (2016) showed that the overwhelming majority of students believed that the main reason why entrepreneurship education was unsatisfactory was that the shortage of innovative and high-quality teachers affected the quality of entrepreneurship curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation